FORMULASI GEL EKSTRAK DAUN SASALADAHAN (Peperomia pellucida (L.) H.B.K) DAN UJI EFEKTIVITASNYA TERHADAP LUKA BAKAR PADA KELINCI (Oryctolagus Cuniculus) - Mappa, Tiara; Edy, Hosea Jaya; Kojong, Novel (PHARMACON, 2013)
Sasaladahan contains saponin, tannin, alkaloid, calcium oxalate, fat, essential oil, flavonoid, steroid, triterpenoid and carbohydrate. Saponin can stimulate the formation of collagen, while tannin and flavonoid have activity as antiseptic and antibacterial. The aims of this research were to determine the quality of Sasaladahan leaves extract gel (Peperomia pellucida (L.) HBK) by varying the concentration of 5%, 10% and 15% and its effect on the healing of burn wound. The quality of gel was test with organoleptic test, homogenity, pH, spreadability and consistency. The effectiveness test of the gel performed on 5 rabbits were divided into 5 treatment groups where each rabbit made 3 burn wound using a hot metal plate with diameter of 20 mm. The first rabbit was given sasaladahan gel with a concentration of 5%, 2nd rabbit given sasaladahan gel with a concentration of 10%, 3rd rabbit given sasaladahan gel with a concentration of 15%, 4th rabbit given a positive control and 5th rabbit given a negative control. The wound diameter be measured every day until day 7. Data were statistically analyzed using One Way Anova. The results show Sasaladahan gel with concentration of 5%, 10% and 15% fulfilled the parameter evaluation of organoleptic test, homogenity, pH and consistency while the results of spreadability test are not yet fulfilled the parameter of a good spreadability (5-7 cm). The result of the effectiveness test of Sasaladahan leaves extract gel show sasaladahan leaves extract gel with concentration of 5%, 10% and 15% have the healing effect on burn wound. Keywords: Gel, Extract, Sasaladahan Leaves, Burn wound, Rabbit